The potential of nature-based solutions for urban soils: focus on green infrastructure and bioremediation - Celletti, Silvia; Poreba, Ludwika; Wawer, Rafal; Padoan, Elio; Comis, Silvia; Bartosiewicz, Beata; Schiavon, Michela (Frontiers in Environmental Science, 2025)
Nature-based Solutions (NbS) offer a promising, sustainable framework for addressing urban environmental challenges by harnessing the intrinsic functions of natural ecosystems. Defined as economically viable strategies inspired by nature, NbS aim to protect, manage, and restore ecosystems for mutual benefits to both people and nature. In urban and peri-urban contexts, NbS, such as green infrastructure and bioremediation, provide effective approaches to mitigating climate change, enhancing soil, air and water quality, reducing urban heat, and restoring ecological balance. Green infrastructure, comprising parks, urban forests, green roofs, and wetlands, has been shown to improve soil quality by enhancing organic carbon, nitrogen, and phosphorus accumulation, as well as fostering biodiversity. Complementarily, bioremediation strategies, including microbial remediation and phytoremediation, have proven effective in decontaminating soils laden with heavy metals, petroleum hydrocarbons, microplastics, and other pollutants, while promoting soil fertility and ecosystem services. Despite their demonstrated benefits, the efficacy of NbS is influenced by environmental factors such as soil pH, temperature, oxygen availability, and pollutant diversity. In addition, while NbS continue to evolve and their integration into urban planning represents a vital step toward creating resilient, healthy, and sustainable cities, their application in urban environments remains fragmented. Therefore, further research is required to optimize NbS interventions, scale up their implementation, and evaluate long-term impacts under urban conditions characterized by anthropogenic stressors. This review examines green infrastructure and bioremediation strategies, highlighting key case studies and evaluating their effects on soil quality and overall remediation outcomes.